2020
DOI: 10.1111/jsr.13066
|View full text |Cite
|
Sign up to set email alerts
|

On the rise and fall of the apnea−hypopnea index: A historical review and critical appraisal

Abstract: The publication of "The Sleep Apnea Syndromes" by Guilleminault et al. in the 1970s hallmarked the discovery of a new disease entity involving serious health consequences. Obstructive sleep apnea was shown to be the most important disorder among the sleep apnea syndromes (SAS). In the course of time, it was found that the prevalence of obstructive sleep apnea reached the proportions of a global epidemic, with a major impact on public health, safety and the economy. Early on, a metric was introduced to gauge th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 88 publications
3
134
0
4
Order By: Relevance
“…According to the results from a meta-analysis that enrolled 129 patients with OSA, exercise training lasting between 12 and 24 weeks resulted in a mean apnea-hypopnea index (AHI) reduction of 6.27 events/h [ 28 ]. The AHI is a clinical sleep parameter that can assess the severity of OSA [ 29 ]. Noteworthy, the exercise-induced reduction in OSA severity was achieved without a significant decrease in body weight [ 28 ].…”
Section: Physical Exercise As a Lifestyle Intervention To Reduce Sleementioning
confidence: 99%
“…According to the results from a meta-analysis that enrolled 129 patients with OSA, exercise training lasting between 12 and 24 weeks resulted in a mean apnea-hypopnea index (AHI) reduction of 6.27 events/h [ 28 ]. The AHI is a clinical sleep parameter that can assess the severity of OSA [ 29 ]. Noteworthy, the exercise-induced reduction in OSA severity was achieved without a significant decrease in body weight [ 28 ].…”
Section: Physical Exercise As a Lifestyle Intervention To Reduce Sleementioning
confidence: 99%
“…Moreover outcome studies have shown, that counting apnoea and hypopnoea events, and summarizing them to an apnoea–hypopnoea index (AHI) is not enough to predict mortality [ 4 ▪▪ ]. In addition, a few treatment studies have shown, that a simple reduction of the AHI may not improve mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few treatment studies have shown, that a simple reduction of the AHI may not improve mortality. Consequently the development of alternative devices and algorithms tries to derive new metrics which might better predict severity of sleep apnoea and may help to phenotype patients to choose a personalized treatment [ 4 ▪▪ ]. Hypoxia and the hypoxic burden are important parameters related to sleep apnoea severity.…”
Section: Introductionmentioning
confidence: 99%
“…However, all clinicians and researchers who have been working in this field since are greatly indebted to the late Christian Guilleminault, who was a passionate pioneer and spent his whole life discovering the many facets of sleep‐disordered breathing and dissecting the complexity of the disease. In this issue, Pevernagie et al report on an historical review and critical appraisal of the metrics currently used to measure sleep apnea (i.e., the apnea–hypopnea index [AHI]) (Pevernagie et al, 2020). This is a very timely and also comprehensive document.…”
mentioning
confidence: 99%
“…A metric conceptualizing sleep apnea and aiming to anticipate its consequences was born. This subsequently gained wide acceptance, although, as suggested by Pevernagie et al (2020), there have been persistent concerns with respect to validation and reproducibility.…”
mentioning
confidence: 99%